PATHOLOGIC COMPLETE RESPONSE (YPT0 YPN0) AFTER CHEMOTHERAPY AND RADIOTHERAPY NEOADJUVANT FOLLOWED BY ESOPHAGECTOMY IN THE SQUAMOUS CELL CARCINOMA OF THE ESOPHAGUS - Nelson Adami ANDREOLLO; Giovanni de Carvalho BERALDO; Iuri Pedreira Filardi ALVES; Valdir TERCIOTI-JUNIOR; José Antonio Possato FERRER; João de Souza COELHO-NETO; Luiz Roberto LOPES (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2018)
ABSTRACT Background: Esophageal squamous cell carcinoma is an aggressive neoplasia that requires a multidisciplinary treatment in which survival and prognosis are still not satisfactory. The complete pathologic response to neoadjuvant chemotherapy and radiotherapy is considered a good prognosis factor, and esophagectomy is indicated. Aim: Survival analysis of cases with pathologic complete response (ypT0 ypN0) to neoadjuvant chemotherapy and/or radiotherapy, submmitted to esophagectomy. Methods: Between 1983-2014, 222 esophagectomies were performed, and 177 were conducted to neoadjuvant treatment. In 34 patients the pathologic response was considered complete. Medical records of the patients were retrospectively reviewed regarding type of chemotherapy applied, amount of radiotherapy, interval between the neoadjuvant therapy and the surgery, body mass index; postoperative complications; hospital admission time and survival. Results: The average age was 55.8 years. Twenty-five patients were subjected to chemotherapy and radiotherapy, and nine to neoadjuvant radiotherapy. The total radiation dose ranged from 4400 until 5400 cGy. The chemotherapy was performed with 5FU, cisplatin, and carbotaxol, concomitantly with the radiotherapy. The esophagectomy was transmediastinal, followed by the cervical esophagogastroplasty performed on a average of 49.4 days after the neoadjuvant therapy. The hospital admission time was an average of 14.8 days. During the follow-up period, 52% of the patients submitted to radiotherapy and chemotherapy were disease-free, with 23.6% of them presenting more than five years survival. Conclusions: The neoadjuvant treatment followed by esophagectomy in patients with pathologic complete response is beneficial for the survival of patients with esophageal squamous cell carcinoma.